Molecular Heterogeneity and Immunosuppressive Microenvironment in Glioblastoma - DeCordova, Syreeta; Shastri, Abhishek; Tsolaki, Anthony G.; Yasmin, Hadida; Klein, Lukas; Singh, Shiv K.; Kishore, Uday (Frontiers in Immunology, 2020)
Glioblastoma multiforme (GBM) is the most aggressive primary brain tumour in adults, with a poor prognosis, despite surgical resection combined with radio- and chemotherapy. The major clinical obstacles contributing to poor GBM prognosis are late diagnosis, diffuse infiltration, pseudo-palisading necrosis, microvascular proliferation and resistance to conventional therapy. These challenges are further compounded by extensive inter- and intra-tumour heterogeneity and the dynamic plasticity of GBM cells. The complex heterogeneous nature of GBM cells is facilitated by the local inflammatory tumour microenvironment, which mostly induces tumour aggressiveness and drug resistance. An immunosuppressive tumour micro-environment of GBM provides multiple pathways for tumour immune evasion. Infiltrating immune cells, mostly tumour-associated macrophages, comprise much of the non-neoplastic population in GBM. Further understanding of the immunological microenvironment of GBM is essential to make advances in the development of immunotherapeutics. Recently, whole-genome sequencing, epigenomics and transcriptional profiling have significantly improved the prognostic and therapeutic outcomes of GBM patients. Here, we discuss these recent genomic advances, the role of innate and adaptive immune mechanisms, and the presence of an established immunosuppressive GBM microenvironment that suppresses and/or prevents the anti-tumour host response.